Development of AR Comics for Differentiated Chemistry Learning: Catalyzing Students' Critical Thinking - Prasetiyani, Nabila; Priatmoko, Sigit; Sudarmin; Cahyono, Edy (IJCER (International Journal of Chemistry Education Research), 2026)
To bridge the gap in visualization and interactivity found in traditional chemistry tools, this study developed an AR-powered comic using differentiated instruction to help students navigate the spatial complexities of molecular geometry while sharpening their critical thinking.The product was developed using the 4D model (Define, Design, Develop, Disseminate) and integrated visual storytelling, interactive 3D molecular visualisations, and an instructional song to support multimodal learning. Five experts validated the media and content, indicating high validity (media = 89.5%; content = 91%). Effectiveness was examined using a one-group pretest-posttest design with 30 Grade 11 students. Shapiro–Wilk results confirmed normal distributions for pretest and posttest scores (p = 0.278; p = 0.324). A paired-samples t-test showed a significant improvement in students’ critical thinking after the intervention (t(29) = -11.524, p < 0.001). Learning gains were moderate (n-gain = 0.40), with the strongest improvements in supposition and integration but inference and decision-making require further reinforcement through targeted scaffolding, such as the inclusion of guided inquiry prompts or interactive decision-making tasks within the AR interface that direct students to evaluate electron pair repulsions and conclude molecular properties based on their 3D observations. Overall, the AR differentiated comic is a promising medium for strengthening critical thinking in chemistry differentiated learning.